Impact of Sustainability Reports Quality and Green Bonds on Financial Performance in Financial Services Company - Sagung Desy Pratami, A.A; Yunita, Irni (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
The rise of sustainable finance is in accordance with the increasing emphasis on the need to implement sustainable development globally. However, inadequate research has been done on how sustainability finance practices impacts a company's financial performance. Through sustainability reports and the issuance of green bonds, this research aims to comprehend how sustainable finance practices affect financial performance. Return on Equity (ROE) serves as an indicator for financial performance in this research.  The 19 financial services companies listed on the Indonesia Stock Exchange comprised the research's population. Path analysis was used to perform the analysis. The findings show that the issuance of green bonds is positively and significantly impacted by the caliber of sustainability reports. However, the financial performance of Indonesian financial service companies is not significantly impacted by the quality of sustainability reports or the issuance of green bonds. The impact of sustainability report quality on the financial performance of Indonesian financial service companies is positively mediated by the issuance of green bonds. The importance of utilizing green bond issuance as a strategic tool to improve the financial results linked to sustainable reporting practices is highlighted by this finding, which offers useful insights for Indonesian financial service institutions.